(untitled) (American Journal of Technology and Applied Sciences, 2024)
193 vaccinated children were observed for 1.5 years. At the age of 2–6 months, 30% of premature and 46% of children with congenital heart defects were vaccinated with the PCV7/PCV13 vaccine; at the age of 7–11 months, 52 and 40%, respectively. In 65% of cases, the PCV7/PCV13 vaccine was administered together with other vaccines in the national preventive vaccination schedule. The frequency of general post-vaccination reactions (increase in body temperature from 37.6 to 38.0°C) was 4%; no local reactions were recorded. No other adverse events were noted in the post-vaccination period.